Detecting Symptom Exaggeration in College Students Seeking ADHD Treatment: Performance Validity Assessment Using the NV-MSVT and IVA-Plus. Issue 3 (4th May 2018) - Leppma, Monica; Long, Daniel; Smith, Megan; Lassiter, Candace
ABSTRACT: The symptoms of ADHD are highly subjective, and there is ample empirical evidence that demonstrates the ease with which impairments in attention can be feigned on many commonly used subjective and objective measures of attention. We examined the combination of two assessment measures, NV-MSVT and IVA+, to screen for performance validity and ADHD symptoms in college students. Results indicated that the NV-MSVT was effective in differentiating between students with potential high impairment, such as ADHD, and possible malingerers. In addition, in vivo clinical data ( N  = 350) resulted in lower validity cut-off scores on the IVA+ than had been previously suggested. Clinical implications and future research are also discussed.